2011
DOI: 10.1002/maco.200905536
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of Ni‐50Cr HVOF coatings on 310S alloy substrates in a metal dusting atmosphere

Abstract: Metal dusting attack has been examined after three 168 h cycles on two Ni-50Cr coatings with different microstructures deposited on 310S alloy substrates by the high velocity oxy-fuel (HVOF) thermal-spray process. Metal dusting in uncoated 310S alloy specimens was found to be still in the initiation stage after 504 h of exposure in the 50H 2 :50CO gas environment at 620 8C. Dense Ni-50Cr coatings offered suitable resistance to metal dusting. Metal dusting was observed in the 310S substrates adjacent to pores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This case is also proved by recent studies in the AMCs that the thicker coating is more effective in hindering the occurrence of through‐pores, resulting in its enhanced corrosion resistance 12. Herein, it should be pointed out that the coating thickness needs a balance since too thick coating holds much more unfavorable defects and lower interfacial strength with the substrate 21.…”
Section: Discussionmentioning
confidence: 99%
“…This case is also proved by recent studies in the AMCs that the thicker coating is more effective in hindering the occurrence of through‐pores, resulting in its enhanced corrosion resistance 12. Herein, it should be pointed out that the coating thickness needs a balance since too thick coating holds much more unfavorable defects and lower interfacial strength with the substrate 21.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of nickel and cobalt HVOF coatings associated with other elements have been reported extensively in literature regarding corrosion resistance improvement [28][29][30][31][32][33], hot corrosion [34,35], and corrosion associated with wear and erosion phenomena [36][37][38], however, the study of pure nickel and pure cobalt coatings obtained by HVOF has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Different coatings have been applied in order to avoid or suppress metal dusting [8][9][10]. However, the protection is only guaranteed, if the coatings are free of defects and pores because metal dusting may start from defects in the coatings [11][12][13].…”
Section: Introductionmentioning
confidence: 99%